Case report: Schnitzler-like syndrome without monoclonal gammopathy - Wesselmann, Anna Sophie; Künstner, Axel; Fähnrich, Anke; Rose, Christian; Lamprecht, Peter; Busch, Hauke; Ludwig, Ralf J.; Recke, Andreas (Frontiers in Immunology, 2023)
Schnitzler syndrome is a rare autoinflammatory disorder characterized by urticarial rash, joint pain, recurrent fever, leucocytosis, elevated C-reactive protein (CRP) and serum amyloid A (SAA), and monoclonal IgM or IgG gammopathy. According to the Strasbourg criteria, both urticarial rash and gammopathy are mandatorily required for the diagnosis of Schnitzler’s syndrome. However, incomplete variants lacking either skin symptoms or monoclonal gammopathy have also been described. Here, we report a case in which the diagnosis of Schnitzler-like syndrome was made despite the absence of gammopathy, based on neutrophilic dermal inflammation, episodic and excessive increase in inflammatory parameters, and prompt response to anakinra, a soluble IL1 receptor antagonist (sIL-1RA). In addition, we detected neutrophil epitheliotropism, which is highly suggestive of autoinflammatory disease. Using whole-exome sequencing, we were unable to find a causative pathogenic mutation but did find several mutations possibly related to the inflammatory processes in this patient. This and other cases highlight that the existing Strasbourg criteria are too strict to capture Schnitzler-like syndromes that may respond well and rapidly to IL1 inhibition. Recurrent episodes of disease with normalization of inflammatory symptoms in the interval, rapid response to anakinra, and neutrophilic epitheliotropism in a lesional skin biopsy may help confirm the diagnosis of Schnitzler-like syndrome.